Risk Stratification as a Predictive Factor for Cephalosporin Allergy: A Case-Controlled Study - Suleyman, Ayse; Toprak, Sadık; Guler, Nermin (International archives of allergy and immunology, 2022)
Compared to penicillin, cephalosporin allergies are less common in children, and their diagnostic approach is less standardized. A recent European Academy of Allergy and Clinical Immunology position paper provided a risk stratification system for patients with suspected β-lactam hypersensitivity reactions. This study aimed to evaluate risk stratification and predicting factors for confirmed cephalosporin hypersensitivity. The case-controlled study included patients with confirmed cephalosporin hypersensitivity (skin tests, n = 53; drug provocation, n = 19). For each patient, 2 age- and gender-matched control subjects were included in the study. Data were retrieved from patients' records and analyzed retrospectively. Risk stratification was performed according to the severity of index reactions, which was initially divided as high and low risk and then further divided as immediate and nonimmediate. According to risk stratification, the patient and control groups were divided as follows: high-risk immediate (66.7% vs. 13%, respectively), high-risk delayed (1.4% vs. 8.3%, respectively), low-risk immediate (16.7% vs. 16%, respectively), and low-risk delayed (15.3% vs. 62.9%, respectively). Immediate reactions (odds ratio [OR]: 12.1, 95% confidence interval [CI]: 9-24.8, p < 0.001) and high-risk reactions (OR: 7.8, 95% CI: 4.1-14.6, p < 0.001) were associated with confirmed cephalosporin hypersensitivity in univariate analysis. Multivariate regression analysis indicated that immediate reactions (OR: 7.5, 95% CI: 3.3-16.8, p < 0.001) and high-risk reactions (OR: 5.2, 95% CI: 2.1-12.9, p < 0.001) were significant risk factors for the prediction of cephalosporin hypersensitivity. This model can be applied in children with suspected cephalosporin allergy. Skin testing provides diagnostic information in high-risk patients with immediate reactions and reduces the need for drug provocation testing in these patients. It is highly likely to confirm the diagnosis of low-risk patients directly with provocation tests without skin tests. High-risk and immediate reactions were found to be predictive factors for confirmed cephalosporin allergy.